(3GdhOGFY GdeUQajI GdfbOjI hESJKeGQgG aj GdESdGes - (3MSf(B, (3YHOGddg GdCejfs ((3LOI(B:s (3OGQ GdTQhb(B,s, 1983)
(3GdhOjYI aj GdTQjYI GdESdGejI hehba GdbGfhf GdhVYj efgG hGdhOGFY GdeUQajI Ydi VhA GdbhGYO hCMcGe GdTQjYI efgG GdESJKeGQ aj GdhOGFY GdeUQajIs
Keywords: (3GdGSJKeGQs; (3GdGSdGes; (3GdHfhcs; (3GdeUGQas; (3GdhGOFYs